Controlled dual delivery of fibroblast growth factor-2 and Interleukin-10 by heparin-based coacervate synergistically enhances ischemic heart repair. (December 2015) - Chen, William C.W.; Lee, Brandon G.; Park, Dae Woo; Kim, Kyobum; Chu, Hunghao; Kim, Kang; Huard, Johnny; Wang, Yadong
Abstract: Myocardial infarction (MI) causes myocardial necrosis, triggers chronic inflammatory responses, and leads to pathological remodeling. Controlled delivery of a combination of angiogenic and immunoregulatory proteins may be a promising therapeutic approach for MI. We investigated the bioactivity and therapeutic potential of an injectable, heparin-based coacervate co-delivering an angiogenic factor, fibroblast growth factor-2 (FGF2), and an anti-inflammatory cytokine, Interleukin-10 (IL-10) in a spatially and temporally controlled manner. Coacervate delivery of FGF2 and IL-10 preserved their bioactivities on cardiac stromal cell proliferation in vitro . Upon intramyocardial injection into a mouse MI model, echocardiography revealed that FGF2/IL-10 coacervate treated groups showed significantly improved long-term LV contractile function and ameliorated LV dilatation. FGF2/IL-10 coacervate substantially augmented LV myocardial elasticity. Additionally, FGF2/IL-10 coacervate notably enhanced long-term revascularization, especially at the infarct area. In addition, coacervate loaded with 500 ng FGF2 and 500 ng IL-10 significantly reduced LV fibrosis, considerably preserved infarct wall thickness, and markedly inhibited chronic inflammation at the infarct area. These results indicate that FGF2/IL-10 coacervate has notably greater therapeutic potential than coacervate containing only FGF2. Overall, our data suggest therapeutically synergistic effects of FGF-2/IL-10 coacervate, particularly coacervate with FGF2 and 500 ng IL-10, for the treatment of ischemic heart disease.